The Role of EFL Teachers' Self-Efficacy and Emotional Resilience in Appraisal of Learners' Success - Xue, Yuxiu (Frontiers in Psychology, 2022)
Different elements in education should be taken into account in the development of education which affects learners’ success. Educators are one of the main elements of any educational program, primarily in mainstream education, and there is considerable research recognizing this and the fact that educators have a significant effect on learners’ success. Therefore, education can be enhanced simply by enhancing educators’ effectiveness. Moreover, because of the importance of educators’ factors, many researchers have emphasized educator attributes over the last 20 years. In an attempt to better explain the interaction between educator-related concepts in the setting of English as a Foreign Language (EFL), educator self-efficacy has a significant impact on the educators’ everyday lives as well as on their learners and is regarded as an important factor in successful education and instruction. Furthermore, as one of the characteristics, teacher resilience is a multifaceted and developmental concept that has newly captured the interest of some scholars, specifically in the last 20 years, allowing educators not only to face difficult situations to survive but also to recover and prosper. To this end, the current review tries to emphasize these two significant factors in regulating learners’ success. Corresponding to this review, some suggestions for further research are provided and pedagogical implications are proposed.